2021
DOI: 10.20506/rst.40.1.3208
|View full text |Cite
|
Sign up to set email alerts
|

Review of critical factors affecting analytical characteristics of serological and molecular assays

Abstract: Analytical characteristics of diagnostic tests, encompassing estimates of repeatability, analytical specificity (ASp) and analytical sensitivity (ASe), are determined during Stage 1 of the World Organisation for Animal Health (OIE) Assay Validation Pathway. Repeatability (an estimate of assay precision and robustness), ASp (measuring only what an assay is intended to measure) and ASe (synonymous with the lower limit of detection) are fundamental parameters that determine future test performance. Importantly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This low variability indicated that the assay would consistently produce duplicate results with high precision because it fell within the acceptable %CV range of raw OD readings. 4 We observed substantial positive correlation between the SAT1 ss-SPCE and the SAT1 VNT log 10 titer for the 4 goat serum dilutions, which was aligned to equally good accuracy. Although VNT is classified as a gold standard test, in our study it appeared that its DSe was lower than that of the ss-SPCE.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This low variability indicated that the assay would consistently produce duplicate results with high precision because it fell within the acceptable %CV range of raw OD readings. 4 We observed substantial positive correlation between the SAT1 ss-SPCE and the SAT1 VNT log 10 titer for the 4 goat serum dilutions, which was aligned to equally good accuracy. Although VNT is classified as a gold standard test, in our study it appeared that its DSe was lower than that of the ss-SPCE.…”
Section: Discussionsupporting
confidence: 60%
“…This low variability indicated that the assay would consistently produce duplicate results with high precision because it fell within the acceptable %CV range of raw OD readings. 4…”
Section: Discussionmentioning
confidence: 99%